Analisis Stres Akademik terhadap School Well Being dan Adversity Intelligence melalui Konselor Sebaya pada Siswa SMK Kelautan Kabupaten Gunungkidul - Erwan Syah, Muhammad; Juliarti Bantam, Dian (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2022)
This study aims to analyze the effectiveness of adversity intelligence and school well-being through peer counselors in Marine Vocational High School students, Gunungkidul Regency. In addition, this research is expected to be the basis for guidance and counseling teaching materials in vocational high schools in the Special Region of Yogyakarta. This research is action research conducted by researchers and in collaboration with related parties that are adapted to the school situation. Peer counselor modules and academic stress measurement tools, adversity Intelligence, school well-being. The measuring instrument used in this study is the result of the development of research by previous researchers. The SWB scale refers to the aspects of having (school conditions), loving (social relations), being (self-fulfillment), and health (health status). While the adversity intelligence scale refers to control, origin and ownership, reach, and endurance. The results of this study include that there is a significant difference in school Well-Being. The experimental group was measured three times, namely Pretest, Posttest, and Follow-Up so that Rational Emotive Behavior Therapy proved effective in improving and changing attitudes, perceptions, ways of thinking, beliefs, and views of irrational bullies making rational views. In addition, perpetrators of bullying can develop themselves and increase self-actualization as optimally as possible through positive cognitive and affective behavior. Peer counselor training positively affects school well-being (SWB) and adversity intelligence (AI) in Marine Vocational High School students, Gunungkidul Regency.